Analisis Persepsi Siswa Terhadap Pembelajaran Literasi Numerasi Di Sekolah Dasar - Esti Novianti; Anneke Dwi Saputri; Antika Putri Rizkiah; Iva Fauziah Haryati; Tia Citra Bayuni (Arfah BHMS Foundation, 2026)
This study aims to analyze elementary school students' perceptions of literacy and numeracy learning, which are important basic competencies in the era of globalization. Numeracy literacy encompasses not only the ability to calculate, but also the understanding and application of mathematical concepts in real-life contexts. Facts show that elementary school students' numeracy literacy skills in Indonesia are still relatively low, this may be caused by negative perceptions of such learning. This study used a quantitative descriptive method with a Likert-scale questionnaire instrument to obtain objective data regarding students' views on the literacy and numeracy learning process. The results of the study indicate that students have a high level of enthusiasm, interest, and understanding of literacy and numeracy activities carried out at school. These findings are expected to serve as a basis for teachers and schools in designing more engaging, contextual, and student- centered learning strategies, thereby increasing motivation and learning outcomes. In addition, this study is expected to contribute to national education policy in strengthening the implementation of numeracy literacy programs in elementary schools.